2013
DOI: 10.1016/j.bbadis.2013.05.032
|View full text |Cite
|
Sign up to set email alerts
|

TNF-related weak inducer of apoptosis (TWEAK) promotes kidney fibrosis and Ras-dependent proliferation of cultured renal fibroblast

Abstract: Tumor necrosis factor-like weak inducer of apoptosis (TWEAK) regulates apoptosis, proliferation and inflammation in renal epithelial cells and plays a role in acute kidney injury. However, there is little information on the chronic effects of TWEAK. We hypothesized that TWEAK may influence renal fibrosis and regulate kidney fibroblast biology, in part, through Ras pathway. We studied a chronic model of experimental unilateral ureteral obstruction in wild type and TWEAK deficient mice, and a murine model of sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
108
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 64 publications
4
108
0
Order By: Relevance
“…In another study, absence of tumour necrosis factor-like weak inducer of apoptosis (TWEAK) delayed the accumulation of myofibroblasts and reduced ECM deposition in the UUO mouse model. On the other hand, TWEAK overexpression promoted renal fibrosis in mice without any kidney damage (48). These results showed the fibrotic actions of TWEAK that should be further investigated in order to understand the mechanisms of a chronic persistent kidney injury model such as the UUO model.…”
Section: Unilateral Ureteral Obstructionmentioning
confidence: 81%
See 2 more Smart Citations
“…In another study, absence of tumour necrosis factor-like weak inducer of apoptosis (TWEAK) delayed the accumulation of myofibroblasts and reduced ECM deposition in the UUO mouse model. On the other hand, TWEAK overexpression promoted renal fibrosis in mice without any kidney damage (48). These results showed the fibrotic actions of TWEAK that should be further investigated in order to understand the mechanisms of a chronic persistent kidney injury model such as the UUO model.…”
Section: Unilateral Ureteral Obstructionmentioning
confidence: 81%
“…It is important to emphasize that these changes are clearly different from the compensatory changes that occur after reduction of renal mass (42). To study renal fibrosis, induced models (surgical and chemical), spontaneous models, genetic models and in vitro models (29,(43)(44)(45)(46)(47)(48) can be used.…”
Section: Animal Models Of Renal Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Transient TWEAK/Fn14 activation is implicated in physiologic tissue repair and regeneration; however, excessive or persistent activation drives pathologic tissue responses in contexts of chronic injury and disease and contributes to progressive tissue damage and degeneration, 4,7 thereby suggesting this pathway as a potential target for intervention. Other than its known expression in endothelial cells 8 and fibroblasts, 9 we recently found expression of Fn14 on mesangial cells, podocytes, and tubular cells, whereas functional studies have implicated TWEAK/Fn14 signaling in the pathogenesis of renal disease. [9][10][11] Previously, we showed that TWEAK induces human kidney mesangial cells, tubular cells, and podocytes to express multiple inflammatory mediators, including RANTES, MCP-1, IP-10, ICAM-1, and VCAM-1, thus promoting kidney infiltration of inflammatory cells and stimulating cellular proliferation.…”
mentioning
confidence: 99%
“…Other than its known expression in endothelial cells 8 and fibroblasts, 9 we recently found expression of Fn14 on mesangial cells, podocytes, and tubular cells, whereas functional studies have implicated TWEAK/Fn14 signaling in the pathogenesis of renal disease. [9][10][11] Previously, we showed that TWEAK induces human kidney mesangial cells, tubular cells, and podocytes to express multiple inflammatory mediators, including RANTES, MCP-1, IP-10, ICAM-1, and VCAM-1, thus promoting kidney infiltration of inflammatory cells and stimulating cellular proliferation. 12,13 In chronic graft-versus-host disease, mice treated with an anti-TWEAK mAb had significantly diminished proteinuria and decreased kidney expression of proinflammatory cytokines.…”
mentioning
confidence: 99%